2012
DOI: 10.3732/ajb.1100499
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of calcium oxalate crystals in floral organs of Araceae in relation to pollination strategy

Abstract: The results are consistent with crystals protecting against insect predation of gametes and embryos. However, the role of crystals in food-bribe staminodia is unclear. They may limit and direct feeding by beetles in some species, while in others they might have no protective role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Pacek and co-workers (Pacek and Stpiczyńska, 2007;Pacek et al, 2012) protection, detoxification, ion balance, tissue support/ plant rigidity, and even the gathering and reflection of light (Franceschi & Nakata, 2005). Coté and Gibernau (2012) tested the function of calcium oxalate crystals in floral organs of Araceae relative to pollination strategy and concluded that these crystals protect the plant against insect predation of gametes and embryos and may possibly limit direct feeding by pollinators of some species. Numerous idioblasts containing raphides, similar to those commonly found in elaiophores of other species of Oncidiinae, were observed in the taxa studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Pacek and co-workers (Pacek and Stpiczyńska, 2007;Pacek et al, 2012) protection, detoxification, ion balance, tissue support/ plant rigidity, and even the gathering and reflection of light (Franceschi & Nakata, 2005). Coté and Gibernau (2012) tested the function of calcium oxalate crystals in floral organs of Araceae relative to pollination strategy and concluded that these crystals protect the plant against insect predation of gametes and embryos and may possibly limit direct feeding by pollinators of some species. Numerous idioblasts containing raphides, similar to those commonly found in elaiophores of other species of Oncidiinae, were observed in the taxa studied here.…”
Section: Discussionmentioning
confidence: 99%
“…prism crystal in Dieffenbachia seguine had size of about 48 μm and about 65 μm in Caladium bicolor and Xanthosoma sp. Prism crystal in Dieffenbachia seguine, Caladium bicolor and Xanthosoma sp could found in inside the thecae, mixed in with the pollen grains [14].…”
Section: Prism Crystalmentioning
confidence: 99%
“…Based on the results of research conducted by Prychid et al [9], plant of the genus Amorphophallus, which was a member of Family Araceae, accumulated CaOx crystals, generally in raphide and druse crystal form. However, it was possible to find other crystal types in Amorphophallus because some species which were grouped in Family Araceae could accumulate other crystal types in their tissue [1,6,[10][11][12][13][14]. Therefore, it was interesting to observe the possibility of a variety of shapes and types of CaOx crystals in porang (Amorphophallus muelleri Blume).…”
Section: Introductionmentioning
confidence: 99%
“…In vegetative organs, which are long-living structures, crystals provide protection against foraging animals, storage of calcium and oxalic acid, regulate Ca levels in plant tissues and organs, provide tissue strength, are involved in the photosynthetic process, and ensure the detoxification of heavy metals (Franceschi and Horner, 1980;Prychid and Rudall, 1999;MolanoFlores, 2001;Franceschi and Nakata, 2005;Kuo-Huang et al, 2007). Similarly, crystals within floral organs are possibly involved in Ca regulation, protection against herbivores, and provide tissue strength given that floral structures are deprived of supporting tissues (Cote and Gibernau, 2012).…”
Section: Calcium Oxalate Crystals In Cardueae (Asteraceae)mentioning
confidence: 99%